2021
DOI: 10.1155/2021/6666699
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Adaptive Neuro‐Fuzzy Inference System Using Metaheuristic Algorithms: Application of Shield Tunnelling Ground Surface Settlement Prediction

Abstract: Deformation of ground during tunnelling projects is one of the complex issues that is required to be monitored carefully to avoid the unexpected damages and human losses. Accurate prediction of ground settlement (GS) is a crucial concern for tunnelling problems, and the adequate predictive model can be a vital tool for tunnel designers to simulate the ground settlement accurately. This study proposes relatively new hybrid artificial intelligence (AI) models to predict the ground settlement of earth pressure ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 68 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Combined prediction models for ground settlement caused by shield tunneling include the combination of metaheuristic algorithms and single prediction models, and the combination of decomposition algorithms and single prediction models. Liu et al 14 compared four different metaheuristic algorithms, differential evolution (DE), particle swarm optimization (PSO), genetic algorithm (GA) and ant colony optimizer (ACO), for optimizing adaptive neuro-fuzzy inference systems (ANFIS). It was found that the use of particle swarm optimization was more effective and the PSO-ANFIS model was used to predict the ground settlement of the shield tunnel with good results.…”
Section: Introductionmentioning
confidence: 99%
“…Combined prediction models for ground settlement caused by shield tunneling include the combination of metaheuristic algorithms and single prediction models, and the combination of decomposition algorithms and single prediction models. Liu et al 14 compared four different metaheuristic algorithms, differential evolution (DE), particle swarm optimization (PSO), genetic algorithm (GA) and ant colony optimizer (ACO), for optimizing adaptive neuro-fuzzy inference systems (ANFIS). It was found that the use of particle swarm optimization was more effective and the PSO-ANFIS model was used to predict the ground settlement of the shield tunnel with good results.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [17,18] employed machine learning algorithms to effectively predict tunnel surface settlement, enhancing the prediction capabilities for surface settlement in urban tunnel construction sites under complex excavation conditions. In addition, the use of combination models with different machine learning methods and various optimization algorithms for predicting ground vibrations caused by blasting and tunnel excavation-induced surface settlement has found applications, effectively improving the prediction of ground settlement [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%